(untitled) (Journal of Production Engineering, 1984)
In this paper, the concept of optimization of tool selection for machining the rotary part is considered as a segment (module) of the system SAPOR -S for automated design of technological processes. The concept for automated tool selection described in the paper as a computer program, and some examples of test results.